2024
DOI: 10.1111/ejss.13488
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of soil management strategies for mitigation of N2O emissions in European arable land: A meta‐analysis

Elena Valkama,
Domna Tzemi,
Ulises Ramon Esparza‐Robles
et al.

Abstract: Soil management strategies involving the application of organic matter (OM) inputs (crop residues, green and livestock manure, slurry, digestate, compost and biochar) can increase soil carbon storage but simultaneously lead to an increase in non‐CO2 greenhouse gas (GHG) emissions such as N2O. Although multiple meta‐analyses have been conducted on the topic of OM input impacts on GHG, none has focused specifically on European arable soils. This study plugs this gap and can assist policymakers in steering Europe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…The database that supports the findings of this study is free to download in Zenodo (https://doi.org/10.5281/ zenodo.10959077). The database should be cited as: Maenhout, P., Di Bene, C., Cayuela, M. L., Govednik, A., Keuper, F., Mavsar, S., Mihelic, R., O'Toole, A., Schwarzmann, A., Suhadolc, M., Syp, A., & Valkama, E. (2024). Knowledge gaps on trade-offs of soil carbon sequestration related to soil management strategies (Version 1.…”
Section: Funding Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…The database that supports the findings of this study is free to download in Zenodo (https://doi.org/10.5281/ zenodo.10959077). The database should be cited as: Maenhout, P., Di Bene, C., Cayuela, M. L., Govednik, A., Keuper, F., Mavsar, S., Mihelic, R., O'Toole, A., Schwarzmann, A., Suhadolc, M., Syp, A., & Valkama, E. (2024). Knowledge gaps on trade-offs of soil carbon sequestration related to soil management strategies (Version 1.…”
Section: Funding Informationmentioning
confidence: 99%
“…The results of a recent meta-analysis show the use of compost was found to reduce N 2 O emissions by 25%. This effect depends on the pedoclimatic conditions, however (Valkama et al, 2024). Zhu et al (2023) suggested that the soil N 2 O emissions are controlled by the ratios of dissolved organic C, easily oxidizable C, particulate organic C and light fraction of organic C-to-total N. Furthermore, higher particulate organic C and hydrolysable ammonium-N increase soil N 2 O emissions (Zhu et al, 2023).…”
Section: Livestock Manure Slurry and Compostmentioning
confidence: 99%